Factors determine job satisfaction among academic staff in University Teknikal Malaysia, Melaka / Nur Amira Ruhaimi - Ruhaimi, Nur Amira (Faculty of Business and Management, 2019)
To become a successful organization, company are facing intensive challenge in improving the employee job satisfaction. Therefore, the purpose of this study is to examine the factors determine job satisfaction of academic staff. The scope of study is Universiti Teknikal Malaysia, Melaka. The factors include pay and promotion, workplace relationship, fairness and workplace environment factor. Total number of academic staff of all branches in UTeM is around 834 employees. Researcher focuses on Technology Campus as it sample of population. The researcher is required to distribute 214 sets of questionnaire. 300 sets of printed questionnaire has been distributed but only 120 sets are able to collected back. Subsequently, SPSS software is used to check collected data and also to produce final results. The result showed that only pay and promotion and fairness that is significant with job satisfaction. Meanwhile, workplace environment and workplace relationship does not have significant relationship with job satisfaction. The recommendation for this study is institution should provide a variety type of pay and promotion and institution should treat every employee equally and fair regardless of their position or status. For future researcher, they can conduct similar study on job satisfaction with largest population and respondent, not only public but also in private institution and include other factors to make the employee satisfied with their current job.